3D Culture Models of Malignant Mesothelioma Reveal a Powerful Interplay Between Photodynamic Therapy and Kinase Suppression Offering Hope to Reduce Tumor Recurrence1. (18th December 2018) - Spring, Bryan Q.; Kessel, David
Abstract: In this issue, Cramer et al . introduce 3D culture models of metastatic mesothelioma to investigate basic cancer biology and new combination therapies for combating this complex and lethal disease. The results suggest that erlotinib‐enhanced photodynamic therapy could further improve the efficacy of intraoperative light‐activation to mop up residual tumor deposits in the clinic following surgical removal of macroscopic mesothelioma metastases.